„Wyjątek” jako kategoria opisu rzeczywistości - Lapis, Włodzimierz (Investigationes Linguisticae, 2004)
What is an exception? Is the exception exceptional or common? Should we be engaged with an exception in this connection? Do exceptions simplify or complicate our lives? In this article we deal with the analysis of these problems and we make an attempt at answering all these questions. We also look for benefits which we can obtain referring to exceptions.